PENGARUH BIMBINGAN KELOMPOK TERHADAP PENINGKATAN EMPATI SISWA DI KELAS X MIPA 3 SMA NEGERI 12 PEKANBARU TAHUN AJARAN 2015/2016 - Maryati Puteri Septami; Tri Umari; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of the increase in emaptistudents in the experimental group. The research method Control Group pre-test-posttest.Subjek in this study were 22 students who have low empathy in class X SMA Negeri12 Pekanbaru.Hasil MIPA research is to test different before and after the implementationof group counseling in the experimental group using the program SPSS formula obtainedresults Wilcoxon Z = -3125 with sig. (2-tailed) of 0002, because sig. (2-tailed) <0.05 then"There are differences in the level of empathy of students before and after the groupcounseling was held in the experimental group". To test the difference in pre-test and posttestin the control group using SPSS formula obtained results Wilcoxon Z = -2679 sig. (2-tailed) 0789 because sig. (2-tailed) <0.05 then "There is no difference in the level ofempathy of students pre-test and post-test in the control group". Then to see the differencesin post test post test experimental group with the control group used formula MannWhitney in SPSS with the result Z = -3983 with results sig. (2-tailed) of 0.000. Karna sig.(2-tailed) 0.000 <0.05 then it can be concluded "there are significant differences betweenthe students empathy post test post test experimental group with the control group" whilethe contribution of group guidance menibngkatkan empathy in students by 55%Keywords: Guidance Group, Empathy,Senior High School